1988
DOI: 10.1104/pp.87.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Abscisic Acid and Indoleacetic Acid before and after Anthesis Relative to Changes in Abscission Rates of Cotton Fruiting Forms

Abstract: Cotton (Gossypium hirsutum L.) fruiting forms exhibit pronounced changes, with age, in their probability of abscission. Large floral buds rarely abscise, but after anthesis the young fruits (boils) have a high probability of abscising. Abscission rate reaches a peak about 5 to 6 days after anthesis and then gradually decreases. An experiment was conducted to try to determine the reason for the rapid and pronounced increase in probability of abscission just after anthesis. Cotton was grown in the field and frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
(7 reference statements)
0
27
0
Order By: Relevance
“…Cotton (Gossypium hirsutum L.), cv Deltapine 61,' was grown in a field at the Western Cotton Research Laboratory in Phoenix as reported earlier (18). Flower buds were harvested 9, 6, and 3 before anthesis; flowers were harvested at anthesis; and bolls were harvested 2, 4, 7, and 9 d after anthesis.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cotton (Gossypium hirsutum L.), cv Deltapine 61,' was grown in a field at the Western Cotton Research Laboratory in Phoenix as reported earlier (18). Flower buds were harvested 9, 6, and 3 before anthesis; flowers were harvested at anthesis; and bolls were harvested 2, 4, 7, and 9 d after anthesis.…”
Section: Plant Materialsmentioning
confidence: 99%
“…it then decreased as free IAA increased. Because these changes in free IAA were inversely correlated with changes in fruiting-form abscission, we suggested that the high concentration of IAA in large flower buds inhibited abscission before anthesis, whereas the low concentration at and for 4 d after anthesis promoted abscission of young bolls (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported that any kind of water stress in soybean tends to accelerate abscission of reproductive organs resulting in decreased yield (Kato, 1964;Doss et al, 1974;Ashley and Ethridge, 1978;Korte et al, 1983). Water deficiency also changes the status of internal hormonal balance in the plant (Mcmichael et al, 1972;Guinn, 1976;Guinn and Brummett, 1988;Guinn et al, 1990). It enhances the rate of ethylene production (Guinn, 1976), increases abscisic acid (ABA) content in young cotton bolls and decreases the free indole-3-acetic acid (IAA) content (Guinn, 1982;Brummett, 1987 and1988).…”
mentioning
confidence: 99%
“…Water deficiency also changes the status of internal hormonal balance in the plant (Mcmichael et al, 1972;Guinn, 1976;Guinn and Brummett, 1988;Guinn et al, 1990). It enhances the rate of ethylene production (Guinn, 1976), increases abscisic acid (ABA) content in young cotton bolls and decreases the free indole-3-acetic acid (IAA) content (Guinn, 1982;Brummett, 1987 and1988). In sesame, abscission could be manipulated by altering the level of IAA and ethylene (Sexton and Roberts, 1982) .…”
mentioning
confidence: 99%